If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19z + -6(4z + -1) = 0 Reorder the terms: 19z + -6(-1 + 4z) = 0 19z + (-1 * -6 + 4z * -6) = 0 19z + (6 + -24z) = 0 Reorder the terms: 6 + 19z + -24z = 0 Combine like terms: 19z + -24z = -5z 6 + -5z = 0 Solving 6 + -5z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -5z = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -5z = 0 + -6 -5z = 0 + -6 Combine like terms: 0 + -6 = -6 -5z = -6 Divide each side by '-5'. z = 1.2 Simplifying z = 1.2
| 20x^2+5.2x-0.5=0 | | 0=8-2y | | 6=2.5(w-2) | | 20x^2=1 | | 6(-6n+5)=138 | | 2r+55=6r+72r | | 8m-15=33 | | 7x+24=14 | | 13=-x/5 | | t-4=15 | | 6y=4x+7 | | y=1.5+3 | | 7(7x+8)+8= | | -51/2m=-22 | | 7z-z=-6z-3-6z | | ((sqrt(x-3))/(x-3))=0 | | Ln(5x-3)=14 | | x-1/4=20 | | (sqrt(x-3))/(x-3) | | t-9=19 | | 16-5x=6-7x | | 11=b/2 | | 9ln(4x)=63 | | (x/6a^3k)-(5ay^2/9dk^2) | | 6(3x-5)=9 | | (1/2)x^4-8=0 | | (-6/5)x^(1/5)=0 | | 2ln(6x)-ln(9)=2 | | 100a-a^2-1234=0 | | a+2/3=-3 | | 5x+3=6x-30 | | 100a-a^2+309=0 |